Work-life balance and workplace adaptation: the effect of organizational support of Malaysian self-initiated repatriates - Kunasegaran, Mageswari; Ismail, Maimunah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This study aimed to investigate the relationship between work-life balance and workplace adaptation of Malaysian self-initiated repatriates. It mainly focused on self-initiated repatriates’ challenges upon their returning and adapting to the local working environment through work-life balance and organizational support. Work-life balance is one of the most debated issues when repatriates decide to return to the home country. A balance approach between work and life maintain the returned self-initiated repatriates in the local organization. The study employed a qualitative method whereby 25 respondents were interviewed from various group of professions who are worked around Klang Valley, Malaysia. The Cross-Cultural Adaptation Theory (Kim, 2001) and Social Exchange Theory (Cropanzon & Mitchel, 2005) were used to explain the relationship between work-life balance, organizational support and workplace adaptation. Four themes were derived from the empirical findings, i) culture variations, ii) work-life conflict, iii) organizational support, and iv) family support. The implications focus on policymakers and practitioners who are involved in preparing self-initiated repatriates for a socialization program through work-life balance approach. This study is an extension of current repatriation literature by focusing on self-initiated repatriates. The empirical analysis of workplace adaptation incorporates both work-life balance and organizational support as a valid perspective of self-initiated repatriates.